2014
DOI: 10.1255/jnirs.1119
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of Partial Least-Squares Models to Change in Sample Temperature: II. Application to Fruit Attributes

Abstract: Partial least-squares regression models were developed using spectra of tomato fruit collected at 15°C and tested on spectra of an independent set of fruit at higher sample temperatures. The influence of sample temperature on the model used to predict fruit dry matter (DM) was manifested primarily in terms of bias, not standard error of prediction. For example, a model for DM created with samples at 15°C had a bias of-0.9% DM and-1.9% DM when used to predict DM in fruit at 25°C and 35°C, respectively. The addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Additionally, the global model showed useful prediction ability, which made temperature fluctuation a negligible interference. Besides, there are many other studies [37][38][39][40][41][42][43] that have proved that the global model can significantly reduce the effect of temperature on NIR measurement. However, the drawback of this approach is that the required data collection is quite a large undertaking because the local temperature model uses a calibration set for a single selected temperature and a validation set for other temperatures, while the global temperature model contains all of the data sets.…”
Section: Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the global model showed useful prediction ability, which made temperature fluctuation a negligible interference. Besides, there are many other studies [37][38][39][40][41][42][43] that have proved that the global model can significantly reduce the effect of temperature on NIR measurement. However, the drawback of this approach is that the required data collection is quite a large undertaking because the local temperature model uses a calibration set for a single selected temperature and a validation set for other temperatures, while the global temperature model contains all of the data sets.…”
Section: Temperaturementioning
confidence: 99%
“…However, the drawback of this approach is that the required data collection is quite a large undertaking because the local temperature model uses a calibration set for a single selected temperature and a validation set for other temperatures, while the global temperature model contains all of the data sets. Based on large scale of data sets, Acharya et al [41] designed several methods of population structuring for detecting the dry matter and color of tomatoes with the aim of producing robust models that take account of sample temperature. It was concluded that temperature compensation created by adding spectra of the same set of samples at different temperatures was overwhelmed by continuing addition of 500 spectra at a uniform temperature, resulting in a model that was not robust to temperature.…”
Section: Temperaturementioning
confidence: 99%
“…However human capacity is developing, e.g., Dr. Umesh Kumar Acharya of NARC obtained a PhD on the use of NIRS in the assessment of fruit quality at Central Queensland University, Australia. 3,4…”
Section: Government and University Sectormentioning
confidence: 99%
“…Fruit consist of approximately 80% water. The IR/NIR spectrum of water is affected by temperature due to an effect on the extent of hydrogen bonding, and this can impact prediction of soluble solids content (SSC) and dry matter (DM) in intact fruit using SWNIRS with the simplest accommodating measure being the inclusion of samples of a range of temperatures into the training sets (Acharya et al, 2014). Given that the spectral information relevant to internal browning may be restricted to the visible region, spectral based measures of internal browning may be free from interference associated with temperature change, however, this issue should be explicitly considered.…”
Section: Introductionmentioning
confidence: 99%